The Role of “La Chica Moderna” in Three Post-Revolutionary Mexican Plays - Saborio, Linda (Latin American Theatre Review, 2012)
Focusing on Concepción Sada, Magdalena Mondragón, and María Luisa Ocampo, this article examines how these three Mexican female playwrights, through their theatrical productions, advocated for women’s advancement in the workplace in a transitioning postrevolutionary Mexican society. In El tercer personaje, Cuando Eva se vuelve Adán, and La virgen fuerte, all three playwrights produce examples of “la chica moderna” through the staging of strong female protagonists who struggle to maintain a profession as doctors without compromising their feminine identity. By acknowledging the valuable participation of professional females in Mexico’s growing capitalist economy and by confirming the femininity of their female protagonists, Sada, Mondragón, and Ocampo offer their audiences an emerging role of “la chica moderna” who is not a masculinized female but instead an empowered female figure capable of participating on an equal level with her male counterparts.